Design de moda e educação não-formal: os fósseis de árvores petrificadas como referência para processos criativos - Debus, Carolina dos Santos (2008)
This research was developed through the Research Line in Education and Arts of the Education Post-Graduation Program, in the Education Center at the Federal University of Santa Maria/RS/Brazil. This research investigated the non-formal education practice through the regional historical patrimony. This patrimony was located into a paleontological area called Chácara das Flores, in Santa Maria/RS, and the research used as basis the petrified tree fossils in the development of creative processes. These creative processes intended to create an alternative space where education and fashion design interacted and socially contributed to preservation and valorization of historical and practical-educative patrimony in design. The review of theoretical ideas was based on non-formal education theories (Freire 1981, 1983, 1992, 1993, 1996; Gadotti 1991, 1997, 2000, 2001; Gohn 1999, 2004), emphasizing the social inclusion, income generation and performance places. It also used the theories of Malfatti and Agostini (2006), Sommer and Scherer (1999), that are related to petrified tree fossils, Environmental Protection Laws and possible cultural, scientific and social contributions. In the same way, this research was based on the ideas of the following authors: Munari (1987, 1990), Redig (1983), Löbach (2001), Lipovetsky (2006) the concepts, visual languages, creative processes and applications. The research methodology was organized from qualitative approach and outlined through a case study with the collaborators of the research, women that live at Chácara das Flores District, in Santa Maria/RS/BRAZIL. This investigative process involved the comprehension and description of the context where they live, as well as the collective arrangement of the knowledge-making of fashion design, creating their engagement with possible changes in a shared and cooperative action. The instrumental used to collect data was composed by documental analysis, semistructured interviews, social-anthropological interviews, real observations, diary notes and portfolio. Through these qualitative-interpretative analysis it was intended to show that these acquirements can improve the society with the return of new possibilities of income generation, consciousness and patrimony preservation, reflecting the new view of fashion design built by the research collaborators in the constitution of their cultural identities.